Risk of cataract in health care workers exposed to ionizing radiation: a systematic review - Della Vecchia, Elena; Modenese, Alberto; Loney, Tom; Muscatello, Martina; Silva Paulo, Marilia; Rossi, Giorgia; Gobba, Fabriziomaria (La Medicina del Lavoro, 2020)
Background: The eye is an important sensory organ occupationally exposed to ionizing radiation (IR) in healthcare workers (HCWs) engaged in medical imaging (MI). New evidence highlights the possible induction of cataract at IR exposure levels to be much lower than expected in the past. Objective: Conduct an updated review on the current evidence on cataract risk in healthcare workers exposed to IR. Methods: Published scientific studies on cataract risk in IR exposed healthcare workers were collected through a systematic search of two biomedical databases (MEDLINE and Scopus). Data from included studies was extracted and summarized. Study quality was also assessed. Results: All 21 eligible studies reported an increased prevalence of cataract, especially posterior subcapsular cataract, in IR exposed  HCWs with a higher prevalence in interventional cardiology staff. Discussion: Our review synthesizes the latest evidence to support the hypothesis of a significantly increased risk of occupational cataract in healthcare workers operating MI and exposed to IR, especially in interventional cardiologists. Data also support a dose-response relationship between IR exposure and the prevalence of opacities, especially posterior subcapsular opacities. Conclusions: Findings highlight the need for effective control measures including appropriate training, adherence to protective procedures, and a constant use of shields and eye personal protective equipment in healthcare workers with optical exposure to IR. Periodic health surveillance programs, possibly including lens evaluation, are also important to monitor cataract risk in these MI operators.